2021
DOI: 10.1002/ejoc.202100484
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of a Hypothetical Macroketone of Migrastatin

Abstract: Danishefsky's macroketone, a simplified analogue of natural product Migrastatin, is one of the lead compounds with potent cancer cell migration inhibition potential. Different biological assays suggest fascin protein as the potential target. Although it was indicated through X-ray co-crystallography where the concerned macroketone analogue was found to bind in the actin-binding sites of fascin, there was a structural discrepancy, as the X-ray co-crystal structure suggested an E-olefin along with inversion of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The hypothetical macroketone, which is an analogue of the migrastatin natural product, plays an effective role as an anti-cancerous agent. Considering the pharmacological importance of this analogue, Choudhury et al 138 in 2021, reported its total synthesis by utilizing the vinylogous Mukaiyama aldol reaction as one of its key steps. Initial steps involved the synthesis of compound 301 and aldehyde 303 from ( S )-4-benzyloxazolidin-2-one 300 and 2,3- O -isopropylidene- l -tartrate 302 by known methodologies.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The hypothetical macroketone, which is an analogue of the migrastatin natural product, plays an effective role as an anti-cancerous agent. Considering the pharmacological importance of this analogue, Choudhury et al 138 in 2021, reported its total synthesis by utilizing the vinylogous Mukaiyama aldol reaction as one of its key steps. Initial steps involved the synthesis of compound 301 and aldehyde 303 from ( S )-4-benzyloxazolidin-2-one 300 and 2,3- O -isopropylidene- l -tartrate 302 by known methodologies.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The hypothetical macroketone, which is an analogue of the migrastatin natural product, plays an effective role as an anti-cancerous agent. Considering the pharmacological importance of this analogue, Choudhury et al 138 in Scheme 39 Synthesis of amphidinolide F 294.…”
Section: Synthesis Of Miscellaneous Natural Productsmentioning
confidence: 99%
“…For that purpose, we began our synthesis from lactone (−)-9 for MOM protection 15 using MOMCl and DIPEA in CH 2 Cl 2 to provide lactone 18, which upon treatment with NaOH in EtOH broke the six-membered lactone and employed the Mitsunobu condition to invert the secondary alcohol stereochemistry. 8 After the Mitsunobu reaction, we ended up with compounds 19 and 18 as a 3:2 non-separable diastereomeric mixture using regular column chromatography techniques. However, using a preparative HPLC technique, both diastereomers were separated, isolated, and characterized.…”
mentioning
confidence: 99%
“…Aldehyde 4 was subjected for the TiCl 4 -mediated diastereoselective aldol reaction with ( S )-4-benzyl-2-oxazolidinone (+)- 5 at −78 °C in CH 2 Cl 2 to afford Evans syn aldol adduct (+)- 6 in 93% yield with 92:8 diastereomeric ratio (dr) . After removal of the chiral auxiliary using LiBH 4 in tetrahydrofuran (THF)/MeOH, the resultant diol (+)- 7 was subjected for Pd-catalyzed lactonization, where N -formyl saccharin acted as a carbonyl source to deliver lactone (+)- 8 in 69% yield. The primary alcohol of lactone (+)- 8 was oxidized by the Jones reagent to attain carboxylic acid (+)- 9 as a pale yellow solid.…”
mentioning
confidence: 99%
See 1 more Smart Citation